Motivasi Belajar Fisika Siswa Di Sekolah Madrasah Tsanawiyah Melalui Penerapan Model Talking Stick - Yennita Yennita; Mitra Roza Afriani; M. Rahmad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2010)
This study aims to determine the increase of students' motivation in learning physics Madrasah Tsnawiyah(MTS) students. The subject matter chosen is sound and learning strategy used was talking stick modelscombined with cooperative learning. The research is a quasi-experimental study with a sample of 72 eighthgrade students of MTS Hasanah Pekanbaru, divided into experimental group and control group. Theinstrument used for data collection was a learning motivation’s questionnaire with indicators: attention,relevance, confidence and satisfaction. From the descriptive analysis, it is found out that the students'motivation in studying physics of experimental group is higher than the control group. Inferential analysisshowed that there was significant improvement of students' motivation in learning physics at the 90%confidence level.